ANALISIS EFEKTIVITAS BIAYA ANTIBIOTIK LEVOFLOXACIN DAN CEFTRIAXONE PASIEN PNEUMONIA DEWASA RAWAT INAP BPJS DI RSM AHMAD DAHLAN KOTA KEDIRI 2024 - Djembor Walujo; Widhi Astutik; Tiara Ningrum (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2026)
The causes of pneumonia include various microorganisms such as bacteria, viruses, parasites, and fungi. This condition can also be triggered by exposure to chemical substances or physical damage to lung tissue. The purpose of this study was to determine which antibiotic is more cost-effective based on therapeutic outcomes and more efficient costs between Levofloxacin and Ceftriaxone in adult hospitalized pneumonia patients who are BPJS Class III participants at RSM Ahmad Dahlan Hospital, Kediri City, in 2024. This study used a retrospective design, by tracing and analyzing patient data from previous periods through the collection of medical record data and hospital financial data. The sample was taken using a purposive sampling technique with a total of 40 patients. Data analysis was conducted using the Average Cost Effectiveness Ratio (ACER) method. The variables analyzed included therapeutic effectiveness and direct medical costs incurred during treatment. The results of the study showed that the effectiveness of therapy in hospitalized pneumonia patients at RSM Ahmad Dahlan in 2024 reached 100%, both in the Ceftriaxone therapy group consisting of 20 patients and in the Levofloxacin group consisting of 20 patients. Based on the ACER calculation results, the most cost-effective therapy in the management of pneumonia was the use of the antibiotic Ceftriaxone with a cost of Rp25,554, which is lower than therapy using the antibiotic Levofloxacin, which has an ACER value of Rp30,914.